Genetic Disorders Preventive Approach & Its Management: An Ayurvedic Review - V. Lokhande, Dr. Smita; B. Patil, Dr. R.; S. Patil, Dr. Swapnil (International Journal of Innovative Research in Medical Science, 2016)
The genetic disorders are the prime obstacles in the development of human being. The causative factors for these disorders are the improper formation of genotype. There are many causative factors for the derangement of genotype. Ayurvedic literature also stated about the genetic disorders as beejdosha vikara, & also there is elaboration about clearance of beej dosha. Hence in present paper the topic has been discussed.